FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN WANITA MENIKAH DI SUMATERA BARAT - Nini Sahara; Idris Idris; Dewi Zaini Putri (Jurnal Ecogen, 2018)
This study aims to analyzes the factor that influence the decision of married women in West Sumatera. Data used is based on the national socio-economic survey in 2016. The research population is married women in West Sumatera. The research sample is 8842 married women. By  using a logistic regression model. The result of the study show that together education, poverty, and residental areas have a significant effect on the decision of married women in West Sumatera  with a Pseudo R2 value of 12,15%. Keywords: education, poverty, residential area, decisions of married women.